2023
DOI: 10.1021/acssensors.2c02862
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Detection for Lithium-Ion Battery Electrolyte Leakage by Rare-Earth Nd-Doped SnO2 Nanofibers

Abstract: The problems of lithium-ion battery (LIB) failure have attracted growing attention since flammable and explosive electrolyte leakage might lead to serious consequences. However, due to the redox-neutral and volatile nature of main electrolyte components, such as dimethyl carbonate (DMC), trace leakages are difficult to detect. Therefore, research on LIB electrolyte sensors is urgent and lacking. Herein, sensors based on rare-earth Nd-doped SnO 2 nanofibers are reported for detecting DMC vapor in LIB. The excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…The acceptor doping of Nd makes the imbalance of positive charge in x%Nd-VS 2 -C, and some sulfur vacancies would be formed inevitably when Nd replaces V in the substrate to keep the electrically neutral. 19 The initial S 2p 1/2 and 2p 3/2 double peaks of VS 2 -C, which are centered at 163.9 and 162.7 eV, moved toward the low binding energy progressively as the Nd amount increased (Figure 4b). The 2p 3/2 band of 3%Nd-VS 2 -C is as low as 162.5 eV, indicating a higher concentration of S vacancies.…”
mentioning
confidence: 98%
“…The acceptor doping of Nd makes the imbalance of positive charge in x%Nd-VS 2 -C, and some sulfur vacancies would be formed inevitably when Nd replaces V in the substrate to keep the electrically neutral. 19 The initial S 2p 1/2 and 2p 3/2 double peaks of VS 2 -C, which are centered at 163.9 and 162.7 eV, moved toward the low binding energy progressively as the Nd amount increased (Figure 4b). The 2p 3/2 band of 3%Nd-VS 2 -C is as low as 162.5 eV, indicating a higher concentration of S vacancies.…”
mentioning
confidence: 98%
“…Tin oxide (SnO 2 ) is a typical n-type semiconductor with wide band gap (Eg = 3.6 eV, 300 K), which is always regarded as an ideal gas sensor material. , There are many studies that have revealed that the structural design and precious metal modification of SnO 2 have a great effect on improving the detection performance of electrolyte-related gases. It is found that the sensing performance of the SnO 2 based gas sensors can be maximized by controlling the surface area, crystal size, porosity, and oxygen vacancies of the materials. In conclusion, SnO 2 is an excellent and adjustable gas-sensitive material and is expected to detect electrolyte vapor at an early stage.…”
mentioning
confidence: 99%
“…Some researchers have used it for electrolyte testing. For example, Wang et al reported that 3% Nd-doped SnO 2 nanofibers showed high response values of 38.13 to 50 ppm DMC at 150 °C. Wan et al reported that a Co/Pd-doped SnO 2 sensor synthesized via a sol–gel method possessed ppb-level sensitivity (165% response to 500 ppb) and quick response/recovery time (66/240 s to 1 ppm) to DMC at 150 °C.…”
mentioning
confidence: 99%
“…Therefore, as a sensor researcher, we stand at a pivotal juncture in environmental stewardship, where it is essential to acknowledge the pivotal role and requirements played by these gas sensors in our fight against climate change. There are primarily three categories for utilizing gas sensors to mitigate and prevent climate change: (i) GHGs tracking and monitoring systems, (ii) sustainable energy gas monitoring, and (iii) energy efficient/self-powered and durable gas sensor systems …”
mentioning
confidence: 99%